Xanthoceras sorbifolia extracts ameliorate dendritic spine deficiency and cognitive decline via upregulation of BDNF expression in a rat model of Alzheimer's disease. (26th August 2016) - Li, Yinjie; Xu, Jikai; Xu, Pu; Song, Shijie; Liu, Peng; Chi, Tianyan; Ji, Xuefei; Jin, Ge; Qiu, Shimeng; Hou, Yapeng; Zheng, Chen; Wang, Lili; et al.
Highlights: XSE showed cognitive-improving effect in AD-like rat models. Dendritic spine density deficits were ameliorated by treatment with XSE. BDNF was up-regulated and RhoA/ROCK2 were inhibited which were involved in the pharmacodynamics of XSE. Abstract: Xanthoceras sorbifolia, a traditional Chinese folk medicine with anti-inflammatory effects, has been used for a long time in China, especially in the Inner Mongolian area for the treatment of rheumatism. Inflammation is one of the main causes of Alzheimer's disease (AD). AD is characterized by aggregation of amyloid β-peptide (Aβ) plaques, neurofibrillary tangle formation, synaptic dysfunction and neuronal loss. To investigate whether Xanthoceras sorbifolia extracts (XSE) improve cognition and protect dendritic spines, we performed behavioral tests to investigate learning and memory in an Aβ25-35 -induced dementia animal model of AD as well as Golgi staining to observe dendritic spine formation in CA1 pyramidal neurons and western blots to test the expression levels of PSD95, BDNF and downstream signaling pathways. Our results indicated that oral treatment with XSE significantly reduced cognitive impairments in behavioral tests (passive avoidance test, novel object recognition test, Y-maze test and Morris water maze test). Golgi staining results revealed that XSE ameliorated dendritic spine density deficits in CA1 pyramidal neurons in the hippocampus. Western blot analysis suggested that XSE upregulated PSD95, which is the major scaffolding protein in synapses. BDNF levels and the ratio of p-TrkB/TrkB increased, and the expression of the RhoA, a member of the Rho-GTPase family, and its downstream target protein ROCK2 decreased in the dementia animal model following treatment with XSE. Therefore, the cognition-improving effects of XSE probably resulted from dendritic spine protection effects through regulation of BDNF signaling pathways.